Transient and Reproducible Loss of Motor-Evoked Potential Signals After Intravenous Levetiracetam in a Child Undergoing Craniotomy for Resection of Astrocytoma. (15th January 2015) - Simpao, Allan F.; Janik, Luke S.; Hsu, Grace; Schwartz, Alan Jay; Heuer, Gregory G.; Warrington, Andrew P.; Rehman, Mohamed A.
Abstract : Transcranial electrical motor-evoked potential (tceMEP) monitoring is used in complex intracranial and spinal surgeries to detect and prevent neurological injury. We present a case of transient, reproducible loss of tceMEPs after an infusion of levetiracetam during craniotomy and tumor resection in a child. Cessation of the infusion resulted in restoration of baseline tceMEPs. When the infusion was resumed at the end of the procedure, a similar decrease in tceMEPs was seen as before, after the infusion was stopped. The surgery and postoperative course proceeded without incident, and the patient experienced a full recovery.